Incidents, accidents and fatalities in 40 years of German helicopter emergency medical system operations - Hinkelbein, Jochen; Schwalbe, Mandy; Neuhaus, Christopher; Wetsch, Wolfgang A.; Genzwürker, Harald (European journal of anaesthesiology, 2011)
Context - Currently, approximately 100 000 helicopter emergency medical service (HEMS) missions for patients are undertaken in Germany each year. Compared to the early years, risk has reduced significantly, but is still higher than commercial aviation or other airborne operations. - Objective - The aim of the present study was to evaluate helicopter accidents and fatalities related to HEMS operations. - Design - Retrospective study of HEMS accidents in Germany. - Setting - Analysis of accidents in the published flight accident reports of the German Federal Agency for Flight Accident Investigation (40-year period from 1970 to 2009). Data were collected by telephone interview with the operators, manual search of publications and by supplemental internet information. - Main outcome measures - Data were analysed per 10 000 missions. For statistical analysis, Fisher[Combining Acute Accent]s exact test was used. A P value less than 0.05 was considered significant. - Results - During the period analysed, a total of 1.698 million HEMS missions (1970 vs. 2009: 61 vs. 98 471) were flown by a mean of 50 ± 27 (1 vs. 81) helicopters. To date, missions resulted in a total of 99 accidents with a mean of 2.4 ± 1.7 accidents per year (range 0-7). The accident rate was 0.57 (0-11.4) per 10 000 missions and the fatal accident rate was 0.11 (0-0.5). Some 64% of missions did not result in any injuries to occupants, whereas 19.2% were fatal. From the accidents analysed, 43.4% were due to collision with an obstacle during landing, take-off or hovering. Landing was the phase of flight most often associated with accidents (44.4%). - Conclusion - The present study is the largest on HEMS accidents and the only one analysing an entire 40-year time course beginning with inception. In comparison to previous data, a significantly lower accident rate per 10 000 missions was found. Gathering data on the early years is nearly impossible, and further analysis is required to calculate the risk of fatality or identify injury patterns.
Gesehen am 14.09.2022